PERAN PEMERINTAH DALAM PENGAWASAN USAHA RUMAH KOS DI KOTA SAMARINDA DITINJAU MENURUT PERATURAN DAERAH KOTA SAMARINDA NOMOR 4 TAHUN 2011 TENTANG PAJAK DAERAH - Maulana Sidik (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT           This study, entitled “The Role of Government in Supervision Enterprises Boarding House Seen In Kota Samarinda Samarinda According to the Regional Regulation No. 4 of 2011 on Local Taxes”.          This study aims to determine the role of the government of Samarinda in Managing Boarding House is located in the city of Samarinda and to know how to maximize the regional revenue through taxes on businesses Boarding House Hotel.          This research was conducted in the Office of Regional Revenue Office Samarinda to conduct interviews with the Field Data Collection and Section Head Section Head of Sector Revenue and retrieve the data related to tax especially regarding the Boarding House Hotel Boarding House. In addition, the study also conducted a study of literature by way of examining the books, literature and laws and regulations relating to the issues that will be discussed in the thesis writer.          Employers in particular public awareness Boarding House in performing the duty to pay taxes on businesses boardinghouse very important role to help the Government of Samarinda to explore local revenue, Lack of communication between the government and the people became one of the factors that cause citizens lack awareness of the tax. One sector that increased income of an area is the tax sector. Because the tax is the source of income of an area. For the Department of Revenue has the authority to manage the tax has made several attempts to improve the management of the boarding house with a room tax of more than 10 that the existing problems can be solved.          Efforts are being made the Regional Revenue Office Samarinda is to be dropped directly into the field to disseminate information on the importance level of kepudulian and public awareness of local taxes and levies, collected data directly to taxpayers and collect taxes on the tax object to follow include other agencies that are interrelated. While the constraints faced by the Regional Revenue Office Samarinda in terms of facilities and infrastructure that less can be an obstacle in supporting employee performance and mobility-related activities of the office. Keywords : Corporate Governance Boarding House, Regulation No. 4 In 2011